(untitled) (Research, Society and Development, 2021)
Self-medicating is the act of taking medication to alleviate symptoms, without any medical advice in the diagnosis, prescription or follow-up of the treatment. Therefore, the objective of this work is to identify the factors associated with the practice of self-medication caused by parents, the most used drugs, the reasons and to report the importance of the rational use of medications. The methodology used is based on a literature review in databases such as: the availability of medical information on the internet creates a favorable environment for the person to make a diagnosis and medicate on their own. These factors made the indiscriminate use of medications one of the main health problems in Brazil. Every medicine has side effects and, when ingested incorrectly, it can cause more harm than good to the body. Among the risks of self-medication, we can mention intoxication and the difficulty in diagnosing certain diseases due to the fact that some medications can mask important symptoms. Currently, many of those responsible for children use self-medication to relieve symptoms such as headache, cold and pain, resorting to home pharmacies, which contain analgesics, colds and anti-inflammatory drugs that may pose a risk to children. In Brazil, as in most countries, drugs are the main intoxication agent. They correspond to 27.86% of the cases registered per year, according to data from the National System of Toxic Pharmacological Information (Sinitox). Of the total number of cases of drug intoxication, children under the age of five represent 35%.